Dynamics of appetite-mediated gene expression in daidzein-fed female rats in the meal-feeding method. Issue 8 (3rd August 2015) - Fujitani, Mina; Mizushige, Takafumi; Bhattarai, Keshab; Iwahara, Asami; Aida, Ryojiro; Segawa, Tomomi; Kishida, Taro
Abstract: We previously found that daidzein decreased food intake in female rats. The present study aimed to elucidate the relationship between dynamics of appetite-mediated neuropeptides and the anorectic effect of daidzein. We examined appetite-mediated gene expression in the hypothalamus and small intestine during the 3 meals per day feeding method. Daidzein had an anorectic effect specifically at the second feeding. Neuropeptide-Y (NPY) and galanin mRNA levels in the hypothalamus were significantly higher after feeding in the control but not in the daidzein group, suggesting that daidzein attenuated the postprandial increase in NPY and galanin expression. The daidzein group had higher corticotrophin-releasing hormone (CRH) mRNA levels in the hypothalamus after feeding, and increased cholelcystokinin (CCK) mRNA levels in the small intestine, suggesting that CCK is involved in the hypothalamic regulation of this anorectic effect. Therefore, daidzein may induce anorexia by suppressing expression of NPY and galanin and increasing expression of CRH in the hypothalamus. Graphical abstract: : Daidzein feeding changes expression of NPY, galanin, and CRH in the hypothalamus and CCK in the small intestine, resulting in the anorectic effect.